2017
DOI: 10.21037/jtd.2017.09.57
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adherence to continuous positive airway pressure in patients with rapid eye movement-only obstructive sleep apnea: a prospective cohort study

Abstract: CPAP adherence is lower among patients with REM-only OSA compared to patients with non-stage specific OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…4 REM-related OSA is used loosely by sleep clinicians when polysomnography (PSG) shows obstructive sleep-disordered breathing events that occur predominantly or exclusively in REM sleep. 5 A common criterion used for diagnosis is the ratio between the apnea-hypopnea index (AHI) during REM and NREM sleep (the AHI-REM/AHI-NREM ratio), where an AHI-REM/AHI-NREM ratio ≥ 2 indicates a preponderance of respiratory events during REM sleep, or REM-related OSA. 5 However, this definition is not accurate if REM sleep duration and NREM-AHI are not considered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 REM-related OSA is used loosely by sleep clinicians when polysomnography (PSG) shows obstructive sleep-disordered breathing events that occur predominantly or exclusively in REM sleep. 5 A common criterion used for diagnosis is the ratio between the apnea-hypopnea index (AHI) during REM and NREM sleep (the AHI-REM/AHI-NREM ratio), where an AHI-REM/AHI-NREM ratio ≥ 2 indicates a preponderance of respiratory events during REM sleep, or REM-related OSA. 5 However, this definition is not accurate if REM sleep duration and NREM-AHI are not considered.…”
Section: Introductionmentioning
confidence: 99%
“…5 A common criterion used for diagnosis is the ratio between the apnea-hypopnea index (AHI) during REM and NREM sleep (the AHI-REM/AHI-NREM ratio), where an AHI-REM/AHI-NREM ratio ≥ 2 indicates a preponderance of respiratory events during REM sleep, or REM-related OSA. 5 However, this definition is not accurate if REM sleep duration and NREM-AHI are not considered. Therefore, we need to use criteria that account for REM sleep duration and NREM-AHI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to determine the appropriate course of management due to the lack of clinical data regarding the aforementioned treatment options for REM-related OSA. Moreover, two recent clinical studies have indicated that it is difficult for patients with REM-related OSA to achieve good adherence, and these patients are occasionally intolerant to continuous positive airway pressure (CPAP) therapy, which is the standard OSA treatment option [7,8]. Hence, we consider it an urgent challenge to collect clinical data for each treatment option for this specific type of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of several factors leads to longer duration and greater severity of oxygen desaturation during obstructive events in REM sleep than in NREM sleep. REM-predominant or REM-only OSA occurs in one-third of patients presenting to clinical sleep disorder services 2,3 .…”
mentioning
confidence: 99%